TEACHERS’ EFFORTS IN APPLYING FORMATIVE ASSESSMENT IN ENGLISH INSTRUCTION FOR EFL ELEMENTARY STUDENTS - Apriani, Eka; Sanjaya, Hengki Kris; Dubey, Shibani Basu; Muthmainnah, Muthmainnah (Universitas Muhammadiyah Palembang, 2026)
This study investigates teachers' strategies for implementing formative assessment in English as a foreign language (EFL) instruction at the primary school level and identifies the challenges encountered. An exploratory qualitative approach was employed, with data collected through classroom observations and structured interviews involving teachers from three primary schools. A classroom observation checklist documented teacher strategies, while structured interviews identified challenges. The findings indicate that teachers employ strategies such as communicating learning objectives, gathering evidence of learning through interactive and digital activities, and providing targeted feedback. Teachers also adapt their instruction based on formative assessment outcomes to meet students’ needs. The primary challenges identified are time constraints, variations in students’ abilities, and students’ limited confidence in self-reflection. The study recommends technological support, increased time allocation, and professional development to enhance formative assessment implementation. These findings offer practical insights for improving EFL instruction at the primary school level.